Collective Defined Contribution Schemes as an Alternative to Pension Plans - Gómez Hernández, Denise; Demmler, Michael (Mercados y Negocios, 2022)
Traditional pension plans, such as defined contribution and defined benefit, face several risks: being the most known, the increase of life expectancy. To reduce this risk, many hybrid pension plans have been proposed, to mitigate this risk. The objective of this study is to explore the financial and actuarial sustainability of a hybrid pension plan known as collective defined contribution (CDC) by accumulating a pension fund with the methodology found in Aon (2020). The results of the simulations in this study show that the replacement rate defined in the design of a CDC pension plan is reached by all the members of the plan. Moreover, through the same pension fund, deficits and gains are financed by it.